Construction of the Apparent Moisture Sink Index for the Movement of the South Asian High and Associated Indicative Significance. Issue 1 (1st January 2021) - Zhang, Sidou; Liu, Shiyin; Zhang, Tengfei
ABSTRACT: Previous studies indicate that the "spring flood" precipitation in northwestern Yunnan is closely related to the movement of the South Asian High (SAH) and the apparent moisture sink ( Q 2 ) in the southeastern Tibetan Plateau (TP). In this study, using 38 years of ERA-Interim daily- and monthly-mean grid data along with 35 years of Gongshan daily precipitation data, the correlation between the movement of the SAH and Q 2 in the southeastern TP was analyzed. Then the Q 2 index (QI) of the SAH movement was constructed, and its impact on the activities of the SAH was analyzed. The results show that the QI affects the vertical transport of latent heat by interfering with the "chimney" effect, which in turn affects the atmospheric vertical motion in the southeastern TP and adjacent areas. This affects the upper 100 hPa wind field, resulting in changes in wind speed and direction in the upper air, the distribution of the geopotential height field, and the intensity and position of the SAH centre. The QI is positively and negatively correlated with the longitude and latitude of the SAH centre, respectively, and positively correlated with the intensity, implying a predictive effect on the movement trend and intensity evolution of the SAH.